The Effect of Corporate Social Responsibility, Profitability, and Leverage toward Tax Aggressiveness with Size of Company as Moderating Variable - Riza Aulia Fitri; Agus Munandar (Binus Business Review, 2018)
This research aimed to examine the influence of Corporate Social Responsibility (CSR), profitability, and leverage toward tax aggressiveness by considering the size of the company as the moderating variable. The population was 111 companies listed on the Indonesian Stock Exchange (BEI) from 2010 to 2015. Determination of the sample used purposive sampling method, and it obtained a sample of 36 manufacturing based on certain criteria. The analysis technique used was the multiple regression analysis. The results show that CSR and leverage have a significant and negative effect influence on the tax aggressiveness of the corporate tax. Meanwhile, profitability does not significantly influence the tax aggressiveness in corporate taxes, and the size of company cannot moderate the influence of CSR, the profitability, and leverage on tax aggressiveness.